Embracing leadership: a multi-faceted model of leader identity development. Issue 6 (3rd August 2015) - Zheng, Wei; Muir, Douglas
Abstract : Purpose: – Leadership development has been replete with a skill-based focus. However, learning and development can be constrained by the deeper level, hidden self-knowledge that influences how people process information and construct meaning. The purpose of this paper is to answer the question of how people construct and develop their leader identity. The authors intend to shed light on the critical facets of identity changes that occur as individuals grapple with existing understanding of the self and of leadership, transform them, and absorb new personalized notions of leadership into their identity, resulting in a higher level of confidence acting in the leadership domain. Design/methodology/approach: – The authors conducted a grounded theory study of participants and their mentors in a lay leadership development program in a Catholic diocese. The authors inductively drew a conceptual model describing how leader identity evolves. Findings: – The findings suggested that leader identity development was not a uni-dimensional event. Rather, it was a multi-faceted process that encompassed three key facets of identity development: expanding boundaries, recognizing interdependences, and discerning purpose. Further, it is the co-evolvement of these three facets and people's broadening understanding of leadership that led to a more salient leader identity. Research limitations/implications: – The model addresses the gap in literature on how leader identity develops specifically. It enriches and expands existing knowledge on leader identity development by answering the question of what specific changes are entailed when an individual constructs his or her identity as a leader. Practical implications: – The findings could be used to guide leadership development professionals to build targeted learning activities around key components of leader identity development, diagnose where people are in their leadership journey, set personalized goals with them, and provide pointed feedback to learners in the process of developing their leader identity. Originality/value: – The authors provide an in-depth and integrative account of the contents and mechanisms involved in the construction of the leader identity. The authors zero in on the critical transformations entailed in the process to establish and develop a leader identity.